2016
DOI: 10.1093/annonc/mdw090
|View full text |Cite
|
Sign up to set email alerts
|

Management of borderline ovarian tumors

Abstract: More studies on BOT are needed and longer follow-up and better characterization of high-risk subtypes are crucial to better understand long-term risk of BOT and avoid the rare but the fatal outcome in those few patients being undertreated by the current management strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
67
0
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 40 publications
2
67
0
10
Order By: Relevance
“…Chemotherapy and radiotherapy may have a negative effect on BOT prognosis and patients' overall health due to toxicity and complications. In addition, there is no clear evidence that chemotherapy can reduce BOT recurrence . Given the unestablished efficacy of chemotherapy and a poor model fit when this variable was included, we excluded chemotherapy from the final model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chemotherapy and radiotherapy may have a negative effect on BOT prognosis and patients' overall health due to toxicity and complications. In addition, there is no clear evidence that chemotherapy can reduce BOT recurrence . Given the unestablished efficacy of chemotherapy and a poor model fit when this variable was included, we excluded chemotherapy from the final model.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that supplemental chemotherapy or radiotherapy did not have benefit in BOT treatment, even in advanced-stage BOT or BOT with invasive peritoneal implants. 27,28 Chemotherapy and radiotherapy may have a negative effect on BOT prognosis and patients' overall health due to toxicity and complications. In addition, there is no clear evidence that chemotherapy can reduce BOT recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BOTs comprise of 10-20% of all ovarian neoplasms 4. The incidence of BOTs is 1.8–4.8 cases per 100,000 females per year 5.…”
Section: Introductionmentioning
confidence: 99%
“…BOTs often occur in young women, however the absence of stromal invasion warrant a better prognosis compared to ovarian carcinoma [8,9]. Neverthless, since the standard treatment of BOTs is usually surgery, the fertility of these women may be affected [10]. Identifying the genetic background for diagnosis and prognosis should avoid a radical resection and help in developing new targeted therapies, especially in younger woman with desire of childbearing.…”
Section: Introductionmentioning
confidence: 99%